Unveil the role of nano-CaCO3 in early shrinkage and tensile properties of cement paste: From experimental work to modeling. (15th August 2022) - Zhang, Lifeng; Lin, Gaohang; Qian, Xiaoqian; Yan, Dongming; Qian, Kuangliang; Ruan, Shaoqin
Abstract: Nanomaterials could promote cement hydration that leads to better strength development, but their impacts on early shrinkage (up to 72 h) are rarely comprehensively researched. This study aims to investigate the effects of nano-CaCO3 (NC) on early shrinkage and the tensile properties of cement paste, which contains various contents of NC. Before the shrinkage modeling, early shrinkage, water losses, bound water contents (BWC) and pore size distributions (PSD) of cement paste were obtained first. In addition, the tensile strength and tensile strain capacity of the samples were also measured. Results show that the addition of NC increased early total/autogenous shrinkage of cement paste, but revealed different impacts on drying shrinkage. Meanwhile, a parameter r s calculated from PSD and water losses was proposed, and greater drying shrinkage of cement paste was seen with the reduction of r s . Further, a quantitative relationship between r s and early drying shrinkage was built based on experimental results and the theoretical derivation, and a total shrinkage model for 1-day was also built relied on r s as well as the relationship between BWC and autogenous shrinkage. Finally, the use of NC may slightly enhance the tensile properties of cement paste, but it may also raise its cracking risk due to its greater early total shrinkage as measured.